Secondary infections caused by ESKAPE group bacteria and impact on the health of patients with Covid-19 complications – an integrative review (Research, Society and Development, 2022)
Introduction: Bacterial resistance described for the ESKAPE group is a considerable problem for global health that results in social, economic and mainly health damages. Objectives: To describe the harm associated with the health of hospitalized patients with complications from COVID-19 inherent to co-infections caused by the ESKAPE bacterial group. Methodology: This is an integrative literature review, studies were searched in the National Library of Medicine National Institutes of Health (PubMed) and Science Direct, using the PRISMA method, articles published between the years 2020 were included and 2021, in English. Results: The sample consisted of 17 articles, in which the occurrence of the ESKAPE group and inherent damage to the health of patients with COVID-19 was detected. Methicillin-sensitive Staphylococcus aureus (MSSA), followed by methicillin-resistant Staphylococcus aureus (MRSA), Klebsiella pneumoniae and Enterococcus spp. were the main bacteria reported. The main damages inherent to the COVID-ESKAPE association were the prolonged hospitalization time, bacterial resistance to antimicrobials and a higher mortality rate. Conclusion: Therefore, the association between the presence of bacteria from the ESKAPE group and the inherent health damages of patients with COVID-19 cannot be underestimated. It is necessary to follow up with new studies to prevent diseases and promote health based on information about the main complications, promoting interventions and reducing the morbidity and mortality of these patients.